(3OhQ GdGSJKeGQ GdQjGVj aj JMbjb GdJhGRf GdeGdj dOi GdeDSSGJ GdQjGVjI GdLRGFQjI (B: (3OQGSI GSJTQGajI dOhGhjf GdeQcHGJ GdeJYOOI GdQjGVGJ s - (3Hf SGde, UdGM GdOjfs; (3HhWGdHj, jMjs; (3eYgO GdJQHjI GdHOfjI h GdQjGVjI, LGeYI GdLRGFQ (B3 s ((3GdLRGFQ s, 2022)
(3JgOa GdOQGSI Edi GdJYQa Ydi OhQ GdGSJKeGQ GdQjGVj aj JMbjb GdJhGRf GdeGdj dOi OhGhjf GdeQcHGJ GdeJYOOI GdQjGVGJ hdgPG GdZQV GSJNOefG GdefgL GdhUaj aj OQGSJfG Ydi YjfI eJchfI ef (B60 (3eSjQ jfJehf Gdi (B08 (3OhGhjf eQcHGJ eJYOOI GdQjGVGJ Ydi GdeSJhi GdhWfj, h GdJj Je GNJjGQgG HTcd YThGFj efJXe, ceG GSJNOefG GSJeGQI GdGSJHjGf dLeY GdHjGfGJ, MjK Gfg h HYO LeY GdfJGFL heYGdLJgG EMUGFjG Je GdJhUd Gdi Gf OhGhjf GdeQcHGJ GdeJYOOI GdQjGVGJ h habG ddEecGfGJ GdeGdjI h GdehGQO GdHTQjI h GdefTBJ GdQjGVjI GdeJGMI HEecGfgG JMbjb GdJhGRf GdeGdj aj ejRGfjJgG HYjOG Yf GdOYe GdeGdj ddOhdI, EPG eG Je JgjFI HjFI JTQjYjI JSeM HPdc, HGdEVGaI Gdi Jchjf ehQO HTQj caA h GdGHJYGO Yf eQcRjI GJNGP GdbQGQ eY JgjFI efTGJgG GdQjGVjI defGaSI GdbWGY GdNGU(B.s
(3OcJhQGIs
Keywords: (3GOGQI GdehGQO GdHTQjI h GdefTBJ GdQjGVjIs; (3GOGQI GdehGQO GdHTQjI h GdefTBJ GdQjGVjIs; (3GdGSJKeGQ GdQjGVjs; (3GdJhGRf GdeGdjs; (3GdeMGSHIs